Active Confirmation Bias in the Evaluative Processing of Food Images. Issue 1 (December 2018) - Ounjai, Kajornvut; Kobayashi, Shunsuke; Takahashi, Muneyoshi; Matsuda, Tetsuya; Lauwereyns, Johan
Abstract Predictive processing is fundamental to many aspects of the human mind, including perception and decision-making. It remains to be elucidated, however, in which way predictive information impacts on evaluative processing, particularly in tasks that employ bivalent stimulus sets. Various accounts, including framing, proactive interference, and cognitive control, appear to imply contradictory proposals on the relation between prediction and preference formation. To disambiguate whether predictive cues produce congruent biases versus opponent mechanisms in evaluative processing, we conducted two experiments in which participants were asked to rate individual food images. The image database included appetitive and aversive items. In each trial, a cue predicted, with varying degrees of reliability, the valence of the impending food image. In both experiments, we found that the ratings exhibited congruent biases as a function of the reliability of the predictive cue, with the highest evaluations following the most reliable positive-valence predictions. Eye prepositioning further showed a selective spatial bias suggestive of response preparation in line with the predictions. The response times also exhibited a pattern of results consistent with selective preparation, producing slow responses following invalid predictions. The data suggested an active form of evaluative processing, implementing a confirmation bias that aims to accommodate the prediction.